A Detailed Survey of Text Line Segmentation Methods in Handwritten Historical Documents and Palm Leaf Manuscripts - Ratheash, R. Spurgen; Sathik, M. Mohamed (International Journal of Computer Sciences and Engineering, 2025)
The revolution of document analysis provides the handwritten palm leaf manuscripts and historical documents, epigraphic into digital. Digital document is available as auto recognition of those historical documents which is the second revolution in document research. Many algorithms are available from the period of the 19th century to the 20th century with the researchers across the world. In order to achieve auto recognition, the line segmentation is a foremost process. Though automatic segmentation of text lines is still a burning research, many technical issues remain unsolved yet. The present survey has been carried out as the survey of newly proposed and modified methods of text line segmentation in palm leaf manuscripts and handwritten historical documents published during the period 2008 – 2018. It could benefit the researchers who do research in handwriting recognitio